Effect of treating latex with some metal ions on storage hardening of natural rubber - Gan, S.N.; Ting, K.F. (Elsevier, 1993)
Storage hardening of natural rubber is a complex phenomenon involving crosslinking reactions due to certain abnormal groups on the rubber chains. The various mechanisms put forward can each account for certain of the experimental observations. Recently, an ionic crosslinking mechanism involving carboxylate and metal ions was proposed. It is being investigated by treating latex with a series of selected cations. While monovalent cations are found to have no effect on the crosslinking reaction, some divalent cations are able to reduce the storage hardening. Certain transition metal ions catalysed the degradation of natural rubber. Infra-red spectra show that the main chain structure remains the same after the degradation, and the abnormal groups appear unaffected.